The Use of Exchange Coupled Atom Qubits as Atomic‐Scale Magnetic Field Sensors. Issue 6 (29th November 2022) - Kranz, Ludwik; Gorman, Samuel K.; Thorgrimsson, Brandur; Monir, Serajum; He, Yu; Keith, Daniel; Charde, Keshavi; Keizer, Joris G.; Rahman, Rajib; Simmons, Michelle Y.
Abstract: Phosphorus atoms in silicon offer a rich quantum computing platform where both nuclear and electron spins can be used to store and process quantum information. While individual control of electron and nuclear spins has been demonstrated, the interplay between them during qubit operations has been largely unexplored. This study investigates the use of exchange‐based operation between donor bound electron spins to probe the local magnetic fields experienced by the qubits with exquisite precision at the atomic scale. To achieve this, coherent exchange oscillations are performed between two electron spin qubits, where the left and right qubits are hosted by three and two phosphorus donors, respectively. The frequency spectrum of exchange oscillations shows quantized changes in the local magnetic fields at the qubit sites, corresponding to the different hyperfine coupling between the electron and each of the qubit‐hosting nuclear spins. This ability to sense the hyperfine fields of individual nuclear spins using the exchange interaction constitutes a unique metrology technique, which reveals the exact crystallographic arrangements of the phosphorus atoms in the silicon crystal for each qubit. The detailed knowledge obtained of the local magnetic environment can then be used to engineer hyperfine fields in multi‐donor qubits for high‐fidelity two‐qubit gates. Abstract : Electron spin qubits in silicon are shown to serve as magnetic field sensors at the atomic scale. The work presents a novel spectroscopy technique where a pair of exchange‐coupled electron spins on phosphorus qubits in silicon is used to probe the local magnetic fields to determine the exact location of nuclear spins within the silicon chip.